Pain assessment strategies in patients with musculoskeletal conditions - M. Carotti; A. Ciapetti; F. Salaffi (PAGEPress Publications, 2012)
Valid and reliable assessment of pain is fundamental for both clinical trials and effective pain management. The nature of pain makes objective measurement impossible. Chronic musculoskeletal pain assessment and its impact on physical, emotional and social functions require multidimensional qualitative tools and healthrelated quality of life instruments. The recommendations concerning outcome measurements for pain trials are useful for making routine assessments that should include an evaluation of pain, fatigue, disturbed sleep, physical functioning, emotional functioning, patient global ratings of satisfaction, and quality of life. Despite the growing availability of instruments and theoretical publications related to measuring the various aspects of chronic pain, there is still little agreement and no unified approach has been devised. There is, therefore, still a considerable need for the development of a core set of measurement tools and response criteria, as well as for the development and refinement of the related instruments, standardized assessor training, the cross-cultural adaptation of health status questionnaires, electronic data capture, and the introduction of valid, reliable and responsive standardized quantitative measurement procedures into routine clinical care. This article reviews a selection of the instruments used to assess chronic musculoskeletal pain, including validated newly developed and well-established screening instruments, and discusses their advantages and limitations.